Faith, freedom, and higher education historical analysis and contemporary reflections - Kemeny, Paul Charles (Eugene, Oregon : Pickwick Publications, 2013)
While debates abound today over the cost, purpose, and effectiveness of higher education, often lost in this conversation is a critical question: Should higher education attempt to shape students' moral and spiritual character in any systematic manner as in the past, or focus upon equipping students with mere technical knowledge? Faith, Freedom, and Higher Education argues that Christianity can still play an important role in contemporary American higher education. George M. Marsden, D.G. Hart, and George H. Nash, among its authors, analyze the debate over the secularization of the university and the impact of liberal Protestantism and fundamentalism on the American academy during the twentieth century. Contributors also assess how the ideas of Dorothy Sayers, C.S. Lewis, Wendell Berry, and Allan Bloom can be used to improve Christian higher education. Finally, the volume examines the contributions Christian faith can make to collegiate education and outlines how Christian institutions can preserve their religious mission while striving for academic excellence.
The soul of the American university revisited / George M. Marsden -- The opening of the Western mind : the emergence of higher education in the "Dark Ages" / Mark W. Graham -- From "old time" Christian college to liberal Protestant university : the forgotten interlude in the history of the secularization of Princeton University / P.C. Kemeny -- Christianity and higher education : why exclusion is a compliment / D.G. Hart -- God and man at Yale revisited / George H. Nash -- The mission of Christian colleges today / Gary Scott Smith -- Unpopular opinions : Dorothy L. Sayers on education / Janice B. Brown -- "What do they teach them in these schools?" C.S. Lewis on reading, education, and psychagogia / James G. Dixon -- Curriculum and culture according to Wendell Berry / Andrew J. Harvey -- Great books, students' souls, and political freedom : reflections on Allan Bloom's The closing of the American mind / Michael Coulter -- How to keep a Christian college Christian / William P. Anderson.
Includes bibliographical references.
Description based on print version record.
Keywords: Church and college -- United States; Christian universities and colleges -- United States; Universities and colleges -- United States -- Religion; Education, Higher -- Aims and objectives -- United States; Education, Higher -- Moral and ethical aspects -- United States; EDUCATION / Higher; Electronic books